(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
In this research, factors that impact the success of teamwork in the online modality were identified and classified. The research was classified as mixed with a sequential exploratory design. As for the data collection and analysis, a systematic review of research on the factors that impact teamwork in the educational context was implemented, emphasizing virtual education. Subsequently, the MICMAC technique was implemented, where there was assistance from experts who, as a group reflection, made it possible to contemplate the interactions between factors to carry out a structural analysis. The results showed four factors that were directly classified as key. The indirect classification showed a displacement of the factors in the plane, compared to the direct classification. This displacement is relevant given that factors classified in one category were classified in a new category and this result is observed only with the indirect relationships that the MICMAC method makes it possible to find.